Feature Size Dependent Manufacturability Influences the Functional Properties of Ti-6Al-4V Micro-Strut Lattices Fabricated through Powder Bed Fusion - O'Keeffe, Conor (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2024)
Powder bed fusion (PBF) additive manufacturing techniques have enabled the fabrication of geometrically complex porous metallic lattice structures. Applied to biomedical implants such lattices offer many advantages over traditional non-porous implants, by allowing tissue ingrowth and more closely recapitulating the stiffness gradients of the native tissue. Despite these advantages, defects inherited from the fabrication process can act to limit structural and mechanical integrity. On account of a reduced feature size, these defects are inherited disproportionately in the micro-strut building blocks of the lattice. This is understood to drive a degradation of mechanical properties compared to traditional bulk-sized components. In this work, we show that this stems from a number of characteristics passed on from the fabrication process. This extends to a disproportionate inheritance of internal porosity, which may arise due to increased cooling rates on account of a higher surface-to-volume ratio; microstructural refinements, which similarly may arise due to increased thermal gradients; and surface defects, which in small diameter struts may account for a much larger portion of the total material volume. By studying these characteristics systematically, and as a function of different strut diameters, we were able to gain an understanding of their individual contribution towards mechanisms of deformation and failure in micro-strut lattices. Furthermore, by adopting standardized micro-strut dog-bone geometries, we were able to isolate geometrical variations between lattice designs, and characterize the bulk mechanical properties of the material, rather than the engineering mechanical properties of the lattice. Among the process inherited characteristics that were investigated, surface defects such as partially adhered powder were shown to be particularly detrimental to both the quasi-static and fatigue properties of micro-struts. These defects act as stress concentrations, which act as critical sites for crack initiation and modify the development of local plasticity; as well as account for a significant portion of the total material volume, and consequentially lead to a reduction in load-bearing capacity. As these defects are largely unavoidable, biomedical implants fabricated through PBF usually require a further surface cleaning post-processing step. However, traditional post-processing techniques such as grinding or polishing are ill-suited to lattice structures due to the lack of a line of sight to internal features. Chemical etching does not have this issue, and in this work was successfully employed for refinement of the as-built surface in lattice structures. Using the micro-strut dog-bone geometries, the resulting improvement in mechanical properties could be characterised alongside the gradual removal of surface defects. In addition to mechanical properties, the overall success of orthopaedic implants is driven by cellular responses at the implant surface. Therefore, this work was also extended to examine the influence of chemical etching on cell-substrate interactions. In vitro assessment revealed that chemical etching influenced osteogenesis. As surface defects were removed, greater cell spreading was observed, suggestive of osteogenic differentiation, and accompanied by enhanced mineralization.
APPROVED